GENETIC PARAMETERS AND CORRELATIONS OF GROWTH AND WOOD PROPERTIES IN Peltophorum dubium - Eduardo Luiz Longui; Israel Luiz Lima; Ana Tereza Durão Galão; José Arimatéia Rabelo Machado; Mauricio Ranzini; Adriano Wagner Ballarin; Miguel Luiz Menezes Freitas; Alexandre Magno Sebbenn (Revista do Instituto Florestal)
The forestry industry uses wood property to assess wood quality and determine the appropriate industrial applications of wood. Understanding the narrow-sense average heritability among progenies ( ) and genetic correlations ( between traits is essential to guide selection of the best progenies in tree improvement. In this study, growth and 16 wood traits at three different positions (pith (PI), middle (MI), and near to the bark (BA)) were measured in a 32-year-old Peltophorum dubium provenance and progeny test established in São Paulo State, Brazil. Traits diameter (DBH) and height (H), and wood traits volumetric retraction (βv), anisotropy index (βt/βr), basic (ρbas) and apparent (ρpab) wood density, compressive strength (fc0), modulus of rupture (MOR), modulus of elasticity (MOE), shear parallel grain (fv0), vessel element length (VEL), vessel diameter (VDI), vessel density (VDE), fiber length (FL), fiber wall thickness (FWT), ray height (RH), ray length (RL), and ray frequency (RF) were used to estimate the  and  between traits aiming to select the best families for increase growth and wood quality. Significant differences among progenies were detected for average positions of wood properties ρbas, ρap, and MOE, ρbas, ρap, fc0, and FL at PI, and VDI and FL at MI positions. The  for these traits was moderate (0.417–0.452). The pairwise  of these traits ranged from moderate to high positives, indicating that selection on any one trait will result in indirect positive genetic gains in the others. This selection strategy is expected to produce wood that is suitable for various uses in the construction and furniture industries.